Quantifying the circular economy in European regions: A bridge towards smart specialisation? - Mirko Kruse; Jan Wedemeier (REGION, 2023)
Circular Economy (CE) aspects are becoming increasingly relevant for a sustainable transition and regional development. Still, a methodology to assess regional performance and interregional differences is exclaimed to be missing at least in the European context. This gap makes it difficult to assess policies and evaluate development patterns. The authors present a methodology to overcome this research gap by including several dimensions of social, environmental, and economic CE aspects. The methodology consists of 29 indicators grouped in six dimensions with data obtained from various data bases. A static and a trend index are calculated to compare European NUTS 2 regions in terms of their current CE status and its development over the last years. The new insights paint a more differentiated picture of regional CE transition highlighting that a segregation is observable not so much between North and South or East and West but more between urban and rural regions. Regarding the practical CE implementation in European regions, the instrument of smart specialisation is discussed.
Keywords: O18; P48; R1; R11; 330; Circular Economy; Smart Specialisation; Transformation; Assessment Methodology; Regional Development